Fast and Effective Method for the Detection of Brain Tumor using Chebyshev Harmonic Fourier Moments - Prashar, A; Upneja, R (International Journal of Computer Sciences and Engineering, 2025)
Brain tumor is a serious type of disorder which is caused by the abnormal cells formation within the brain. The identification of brain tumor and further analysis from the Magnetic Resonance Imaging (MRI) is a vigorous process and in this paper fast and effective method is used for the tumor detection by using Chebyshev Harmonic Fourier Moments (CHFMs) on segmented magnetic resonance brain images. The proposed method is free from any overflow situations as it does not involve any factorial term and also free from underflow situations as no power terms are involved. Before the segmentation process, the feature set is extracted by using 2D Continuous Wavelet Transform (2D-CWT). Asymmetry in the MR brain image is analyzed by using CHFMs on each of the tissues segmented in the head. Once the presence of asymmetry is confirmed, it leads us to the diagnosis of the tumor. After the presence of tumor, the region of tumor is extracted by using Polar Harmonic Transforms (PHTs) as these transforms are found to be good descriptors in the field of image analysis and impose less computational complexity due to the absence of any factorial term in the calculation of radial kernels. The effectiveness of the proposed method is analyzed by doing experiments on 35 MR brain images with tumor and 65 normal MR brain images. It is observed that that the proposed method and technique is successful in 97% cases